The Role of Celebrity Endorsers in Interest in Buying Local Beauty Products on Tik Tok: Parasocial Interaction Theory of the Millennial Generation in Jakarta - Khaerunnisa, Divya Hangesty (UNIVERSITAS PAKUAN, 2020)
Changes in media using the internet make it easier for various human needs not only in communicating. Humans can do anything with the internet, where the internet seems to be a primary human need because it fills almost all spaces of life. This study aims to determine how the influence of the role of a celebrity endorser has on consumer buying interest in local Indonesian beauty products through the perspective of parasocial interaction related to the experience of the millennial generation in Jakarta using the systematic literature review (SLR) method. The Systematic Literature Review (SLR) in this study has collected data from several journal articles regarding Parasocial Interaction Theory and its application to the context of the experience of buying interest in the millennial generation. This study reviews previous research and from this study it was concluded that the interaction of celebrity endorsements on social media turned out to have a big influence on sales of local beauty brands. The role of Celebrity Endorsement turned out to be quite a high attraction for respondents or consumers in developing their purchase intention for local beauty products. Meanwhile, celebrity credibility shows a moderate impact on the millennial generation. This also shows that there is Celebrity Endorsement in the marketing strategy which triggers the millennial generation to use a particular product and increases purchase intention.